Appraisal of Women Empowerment through DWCRA - An Empirical Study of Andra Pradesh - Devi, R. Uma (Journal of Commerce and Trade, 2012)
Empowerment of women has emerged as an important issue in recent times. Empowering women particularly rural women is a challenge. Women are economically empowered through small scale entrepreneurship programme with the help of Self Help Movement. Economic empowerment of women led to the empowerment of women in several aspects such as socio- economic opportunity, property rights, political representation, social equality, personal rights, family development, and community development and at last the nation development. DWCRA with exclusive focus on economic empowerment of women provides all these inputs by considering women as critical to development.Self Help movement through savings has been taken up as a mass movement by women. There are about 5.79 lakh women Self-Help Groups in Andhra Pradesh covering nearly 74.58 lakh rural poor women. On this backdrop, an attempt is made to analyze the role of DWCRA groups in the empowerment of women in Andhra Pradesh.